Adsorptive Desulphurization Of Dibenzothiophene By Using Bentonite-Based Adsorbent - Suri, Muhammad Farhan Hakim (Universiti Sains Malaysia, 2022)
Adsorptive desulphurization has been one of the focus of the researchers over the past decade due to its lower energy consumption, environmentally friendly, and cheaper alternative. In this study, bentonite-based adsorbents are used to reduce the concentration of dibenzothiophenes in the model oil. Five different kinds of bentonite-based adsorbents; pure bentonite, acid-washed bentonite, Ni-bentonite, sodium-bentonite, and magnesium-bentonite, were prepared. These five bentonite-based adsorbents were tested under normal ambient conditions, and the result showed that Ni-bentonite has the highest desulphurization at 49.8%. Then, Ni-bentonite was tested in two different ranges DBT concentration; 100 ppm and 1000 ppm. The result shows that Ni-bentonite performed poorly in 100 ppm DBT model oil. Therefore, 1000 ppm of DBT model oil is chosen instead. Then, Nickel-bentonite is subjected to different parameters tests. In the effect of adsorbent dosage study, the result showed that the optimum desulfurization of Ni-bentonite dosage is 1.0 g. For the effect of temperature study, the result showed that the optimum temperature for desulphurization is 40°C. Regarding the effect of contact time between the adsorbent and adsorbate, the result showed that the optimum contact time for desulphurization 2 hours. The last parameter tested is the effect of the percentage of metal loading. The result showed that 30% of nickel loading provides the highest desulphurization percentage, at 55%. In the present study, the adsorption process was found to fit the Langmuir isotherm model better than Freundlich isotherm.